Efektivitas Health Education Berdasarkan Teori Health Promotion Model Dan Strategi Self Monitoring Terhadap Kepatuhan Penatalaksanaan Hipertensi Pada Pasien Hipertensi - Aprilia; Tri Cahyo Sepdianto; Marsaid Marsaid; Imam Subekti (Jurnal Keperawatan Muhammadiyah, 2026)
Objective: Currently, many hypertension sufferers tend not to comply with their prescribed treatment. Low adherence to hypertension treatment is a significant obstacle in hypertension management. This study aims to analyze the effectiveness of health education and self-monitoring strategies on hypertension management compliance. Methods: The study used a quasi-experimental design with a two-group pre-post test approach, involving 40 respondents who were divided into treatment and control groups through purposive sampling. Health education used booklets and animated videos. The adherence instrument used the MMAS-8, while monitoring of signs, symptoms, and risk factors was recorded using a hypertension control card. Data analysis was performed using the Wilcoxon test and the Mann–Whitney test. Results: The results of the study showed that in the pre-test, the average level of compliance of the treatment group was low (5) and the control group was low (2.52). In the post-test, the average level of compliance of the treatment group increased significantly (7.51) and the control group remained low (1.83). The Wilcoxon test results obtained a p value = 0.00 (<0.05), meaning there was a significant difference in the level of compliance pre and post in the treatment group. Meanwhile, the Mann-Whitney test results obtained a p value = 0.000 < (0.05), meaning there was a significant difference in the level of compliance post between the two groups, so it was concluded that Health education based on the Health Promotion Model and self-monitoring strategies were proven effective in increasing compliance with hypertension management. Conclusion: It is hoped that community health centers and health workers can implement health education using booklets and videos to increase understanding of hypertension management and use the Self-Control Card to monitor signs, symptoms and risk factors in hypertension sufferers.